Metagenomics Analysis Reveals Compositional and Functional Differences in the Gut Microbiota of Red Swamp Crayfish, Procambarus clarkii, Grown on Two Different Culture Environments - Chen, Xi; Fan, Limin; Qiu, Liping; Dong, Xinxu; Wang, Qing; Hu, Gengdong; Meng, Shunlong; Li, Dandan; Chen, Jiazhang (Frontiers in Microbiology, 2021)
Structure and function of intestinal microorganisms are closely related to host metabolism, development, physiology and health. Metagenomics analyses was applied to unveil the taxonomic composition and functional diversity of microbiota in the intestine of red swamp crayfish from pond culture environments and rice-crayfish cultivation environments. The results showed that Firmicutes and Proteobacteria were two most abundant components of microorganisms. And bacterial and archaeal communities rather than fungal and viral communities showed significantly differences between these two environments. The abundance of genes involved in pathways focused on Genetic information processing and Human Diseases decreased in gut of red swamp crayfish from rice-crayfish cultivation environment. Especially the abundance of two genes, K13730 and K08303, that were related to the invasion of epithelial cells by two kinds of bacteria, Listeria monocytogenes and Helicobacter pylori respectively decreased in this culture envrionment. Besides, the rice-crayfish cultivation environment has the tendency of reducing the abundance of Glycosyltransferases (GTs), the most abundant carbohydrate-active enzyme in the present study, and increasing the abundance of GHs, and it has the ability of reducing the abundance of GT2.